المشكلات السلوكية لدى اطفال الروضة من وجهة نظر المربيات بولاية الاغواط - بن سليمان صفاء; سناء رانيا العابد; الامين عياط (My University, 2023)
The study aimed to identify the most important behavioral problems among kindergarten children from the point of view of nannies in the state of Laghouat, as it has become a characteristic of some students to have abnormal behaviors. In our study, we relied on the descriptive and analytical approach. We also relied on a scale of behavioral problems among children presented to kindergarten teachers in the state of Laghouat, and it was analyzed. The results were based on the SPSS program and the study reached the following results: The behavioral problems that the child suffers from in the honesty scale is the frequent going to the toilet more than once per class, which is basically considered a problem for many children, as educators suffer from it, and this is because the children imitate each other and therefore it is a behavioral problem. There are no statistically significant differences in behavioral problems among kindergarten children due to the nanny’s experience variable Keywords: behavioral problems - kindergarten child - kindergarten teacher